Taxonomic review of the genus Tarika Moore with descriptions of six new species from Nepal, China and Indochina (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V.; Saldaitis, Aidas; Černý, Karel; Huang, Si-Yao (Zootaxa, 2023)
The Asiatic footman moth genus Tarika Moore, 1878, which used to be considered as monotypic is reviewed. Six new species are described: T. annapurna sp. n. (Сentral Nepal), T. erlanga sp. n. (China: Sichuan), T. reducta sp. n. (North Thailand), T. danieli sp. n. (China: Yunnan, Sichuan, Fujian, Shandong), T. kinha sp. n. (North Vietnam and China: Yunnan), and T. biserratula sp. n. (China: Hunan). Lectotypes are designated for Lithosia varana Moore, 1865 and Tarika nivea Moore, 1878. Adults, male and female genitalia are illustrated.